TRANSPARANSI PENGELOLAAN ANGGARAN DAERAH DI SATUAN KERJA PERANGKAT DAERAH (SKPD) KABUPATEN BULUKUMBA TAHUN 2014 - Latief, Firmanto (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2016)
The main topic that will be discuss in this research is about regional financial transparency management in the Satuan Kerja Perangkat Daerah (SKPD) of Bulukamba region, particularly at the Education, Youth and Sport Authorities, Health Authorities, Regional Finance Management Authorities, and Bina Marga Authorities of Bulakamba region. This research conducted to get further understanding of the transparency of regional financial management in the Satuan Kerja Perangkat Daerah and some factors that work on the transparency implementation. The method that use in this research is a compounding between  qualitative and quantitative methods, and the sample number in this research are 60 people which using purposive sampling method.  Based from some indicators, researcher find that cumulative index of the transparency of the financial management which organized by Education, Youth and Sport Authorities of Bulakamba region is 2.02 that categorize as satisfactory level. Cumulative index of the transparency of the financial management which organized by Regional Finance Management Authorities is 2.81 that categorize in satisfactory level. Cumulative index of the transparency of the financial management which organized by Health Authorities is 1.98 and Cumulative index of the transparency of the financial management which organized by Bina Marga Authorities of Bulakamba region is 2.09 that both also categorize in satisfactory level.